Clinical and genomic features of non‐small cell lung cancer occurring in families. Issue 10 (3rd March 2023) - Miyabe, Shingo; Ito, Shin; Sato, Ikuro; Abe, Jiro; Tamai, Keiichi; Mochizuki, Mai; Fujimori, Haruna; Yamaguchi, Kazunori; Shindo, Norihisa; Shima, Hiroshi; Yamazaki, Tomoko; Abue, Makoto; et al.
Abstract: Background: Exposure to environmental carcinogens, such as through smoking, is a major factor in the carcinogenesis of non‐small cell lung cancer (NSCLC). However, genetic factors may also contribute. Methods: To identify candidate tumor suppressor genes for NSCLC, we included 23 patients (10 related pairs and 3 individuals) with NSCLC who had other NSCLC‐affected first‐degree relatives in a local hospital. Exome analyses for both germline and somatic (NSCLC specimens) DNA were performed for 17 cases. Germline exome data of these 17 cases revealed that most of the short variants were identical to the variants in 14KJPN (a Japanese reference genome panel of more than 14 000 individuals) and only a nonsynonymous variant in the DHODH gene, p.A347T, was shared between a pair of NSCLC patients in the same family. This variant is a known pathogenic variant of the gene for Miller syndrome. Results: Somatic genetic alterations in the exome data of our samples showed frequent mutations in the EGFR and TP53 genes. Principal component analysis of the patterns of 96 types of single nucleotide variants (SNVs) suggested the existence of unique mechanisms inducing somatic SNVs in each family. Delineation of mutational signatures of the somatic SNVs with deconstructSigs for the pair of germline pathogenic DHODH variant‐positive cases showed that the mutational signatures of these cases included SBS3 (homologous recombination repair defect), SBS6, 15 (DNA mismatch repair), and SBS7 (ultraviolet exposure), suggesting that disordered pyrimidine production causes increased errors in DNA repair systems in these cases. Conclusion: Our results suggest the importance of the detailed collection of data on environmental exposure along with genetic information on NSCLC patients to identify the unique combinations that cause lung tumorigenesis in a particular family. Abstract : Whole exomes of 17 patients with NSCLC who had other NSCLC‐affected first‐degree relatives were analyzed for both germline and somatic (NSCLC specimens) DNA. Germline exome identified a nonsynonymous variant in the DHODH gene, p.A347T in a pair of NSCLC patients in the same family. This variant is a known pathogenic variant of the gene for Miller syndrome. Principal component analysis of the patterns of 96 types of single‐nucleotide variants (SNVs) suggested the existence of unique mechanisms inducing somatic SNVs in each family. Somatic mutational signatures of germline DHODH mutated cases showed DNA repair deficit‐related signatures, suggesting that disordered pyrimidine production causes increased errors in DNA repair systems in these cases.